Aula invertida y su influencia en el proceso de enseñanza - aprendizaje de los estudiantes de la Escuela Juan E. Verdesoto, Babahoyo. 2022 - Miranda Domínguez, Valentina (2023)
The investigative work presented below had the purpose of determining the way in which the flipped classroom influences the teaching-learning process of the students of the Juan E. Verdesoto School of the Babahoyo canton in the year 2022 and for which it was carried out. carried out a descriptive documentary research and a survey through quantitative research in which it was possible to obtain the results that help to fulfill the proposed objectives. As well as, the explanatory research methodology that helped to determine the level of relationship between the variables and whose result was that of a medium relational level with 59.4%. In this way it can be verified that the flipped classroom influences the teaching-learning process of the students by generating the initiative to build their own concepts based on the search for information on their own and aiming at self-learning and supported by the use of ICT for a more innovative academic training and to create people with digital skills that will be able to function actively in today's society.